2019
DOI: 10.1155/2019/8130481
|View full text |Cite
|
Sign up to set email alerts
|

Pueraria lobata and Daidzein Reduce Cytotoxicity by Enhancing Ubiquitin-Proteasome System Function in SCA3-iPSC-Derived Neurons

Abstract: Spinocerebellar ataxia type 3 (SCA3) is an autosomal dominant neurodegenerative disorder caused by a CAG repeat expansion within the ATXN3/MJD1 gene. The expanded CAG repeats encode a polyglutamine (polyQ) tract at the C-terminus of the ATXN3 protein. ATXN3 containing expanded polyQ forms aggregates, leading to subsequent cellular dysfunctions including an impaired ubiquitin-proteasome system (UPS). To investigate the pathogenesis of SCA3 and develop potential therapeutic strategies, we established induced plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 73 publications
2
20
0
Order By: Relevance
“…Caspase-3 activity was also reduced, which prevented polyQ-induced cell death [ 55 ]. These findings were in line with another study by Chen et al [ 56 ] using an in vitro model of SCA3 with MG132-induced pluripotent stem cells (iPSCs). Pre-treatment with 50 μM daidzein for 24 h restored proteasome activity in the cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Caspase-3 activity was also reduced, which prevented polyQ-induced cell death [ 55 ]. These findings were in line with another study by Chen et al [ 56 ] using an in vitro model of SCA3 with MG132-induced pluripotent stem cells (iPSCs). Pre-treatment with 50 μM daidzein for 24 h restored proteasome activity in the cells.…”
Section: Discussionsupporting
confidence: 91%
“…Chou et al [ 57 ] reported that the activation of A 2A receptor by T1-11 and JMF-1907 could enhance proteasome activity and promote degradation of ubiquitin proteins. Similar findings were later reported by Chen et al [ 55 , 56 ] using puerarin and daidzein compounds extracted from R. glutinosa and P. lobata . Inhibition of A 2A receptor using an A 2A antagonist blocked the effects induced by T1-11 and JMF-1907.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Expanded ATXN3 localizes more readily to the nucleus, forming intranuclear aggregates that contribute to neuropathology [72]. The expanded protein is still able to bind ubiquitin in hiPSC-derived neurons [22] and shows normal proteasome activity, with increased sensitivity for proteasome inhibition [73]. This hinted towards toxic gain-of-function rather than a loss-of-function of the protein.…”
Section: Sca3 and Atxn3mentioning
confidence: 99%
“…Recently, these phenotypes have been replicated by Thiruvalluvan et al [75], who additionally showed that aggregates were not formed in NSCs challenged with glutamate. Also, Chen et al showed, by a filter trap assay, that unstimulated SCA3 neurons contained 1C2-positive insoluble protein, while cell viability was not affected [73]. However, others have not been able to reproduce these phenotypes [22,76].…”
Section: Sca3 and Atxn3mentioning
confidence: 99%